Recommendations of the thoracic imaging section of the German radiological society for clinical application of chest imaging and structured CT reporting in the COVID-19 pandemic = Empfehlungen der AG Thoraxdiagnostik der Deutschen Röntgengesellschaft zur klinischen Anwendung der Thoraxbildgebung und strukturierten CT-Befundungbei COVID-19-Pandemie - Vogel-Claussen, Jens; Ley-Zaporozhan, Julia; Agarwal, Prerana; Biederer, Jürgen; Kauczor, Hans-Ulrich; Ley, Sebastian; Kühl, Hilmar; Mueller-Lisse, Ullrich G.; Persigehl, Thorsten; Schlett, Christopher L.; Wormanns, Dag; Antoch, Gerald; et al. (RöFo, 2020)
This information provided by the Thoracic Imaging Section of the German Radiological Society is intended to give physicians recommendations on the use of thoracic imaging procedures in the context of the current COVID-19 pandemic. It represents the consensus of the authors based on the previous scientific knowledge and is intended to provide guidance for unified, structured CT reporting if COVID-19 pneumonia is suspected. The recommendations presented correspond to state of knowledge at the time of print and will be updated according to the results of ongoing and future scientific studies. Key Points: Citation Format